Peningkatan Pengetahuan Masyarakat akan Fungsi Hutan untuk Mewujudkan Pengelolaan Hutan Lestari di Desa Kuala Tolam, Kabupaten Pelalawan, Provinsi Riau - Lestari, Ika; Maryani, Maryani; Agustina, Dinda Tri; Ikhsani, Hanifah; Nugraha, Lefdi Agung; Mohta, Gandhiko; Allasselcida, Anesha; Putra, Agung Kartika; Sabri, Erwanda Trio Bintan; Qomar, Nurul; Pebriandi, Pebriandi; Irfani, Ewi (Unri Conference Series: Community Engagement, 2025)
Kuala Tolam Village, Pelalawan Regency, Riau Province, is one of the regions that still possesses significant peatland forests, which are ecologically, socially, and economically important. However, pressures from plantation expansion, land conversion, and limited community knowledge about forest functions have made this area vulnerable to degradation. This community service activity aimed to enhance public knowledge of the importance of forests. The method employed was socialization through an educational, participatory, and interactive approach combined with small group discussions. The respondents in this activity were stakeholders involved in community deliberations with the Siak Pelalawan Landscape Program in the context of forming a collective commitment to maintain forest functions and areas. The results of this activity showed an increase in community knowledge about forest functions as measured by several aspects, namely forest definition, forest types, and forest functions. Community understanding of the definition of forests increased by 39%, knowledge of forest types around Kuala Tolam Village increased by 36%, and knowledge of forest functions increased by 30%. These findings indicate that the socialization and educational approaches applied were successful in raising public awareness of the importance of forests in supporting the community’s commitment to preserving forest functions and areas. Furthermore, the formation of such commitment, supported by enhanced knowledge and understanding, is expected to serve as a strong foundation for establishing a forest patrol and monitoring team in Kuala Tolam Village, Pelalawan Regency.